2017
DOI: 10.1149/2.1311712jes
|View full text |Cite
|
Sign up to set email alerts
|

Freeze Tape Cast Thick Mo Doped Li4Ti5O12Electrodes for Lithium-Ion Batteries

Abstract: Lithium titanate (Li 4 Ti 5 O 12 ) powders with and without molybdenum doping (LTO and MoLTO respectively) were synthesized by a solid-state method and used to fabricate electrodes on Cu foil using a normal tape-cast method and a novel freeze-tape-cast method. Modest molybdenum doping produces a significant electronic conductivity increase (e.g. 1 mS cm −1 for MoLTO vs 10 −7 mS cm −1 for LTO) that is thought to reflect a partial Ti 4+ reduction to Ti 3+ with charge compensation by the Mo 6+ dopant, producing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…This seems to be caused by mass transport limitations of lithium ions in the electrolyte phase and restricted electron transport in the solid phase . Research therefore focuses on the structuring of electrodes, e.g., by laser post‐processing steps or by new processing methods to provide pathways from the electrode surface to the substrate for faster Li‐ion transport . Though a broad knowledge base about transport limitations and tailoring of electrode porosity exists, the significant influence of the electrode production process, namely speaking of the coating and drying conditions on electrode microstructure and cell performance, is often not considered …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This seems to be caused by mass transport limitations of lithium ions in the electrolyte phase and restricted electron transport in the solid phase . Research therefore focuses on the structuring of electrodes, e.g., by laser post‐processing steps or by new processing methods to provide pathways from the electrode surface to the substrate for faster Li‐ion transport . Though a broad knowledge base about transport limitations and tailoring of electrode porosity exists, the significant influence of the electrode production process, namely speaking of the coating and drying conditions on electrode microstructure and cell performance, is often not considered …”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Research therefore focuses on the structuring of electrodes, e.g., by laser post-processing steps or by new processing methods to provide pathways from the electrode surface to the substrate for faster Li-ion transport. [8][9][10][11] Though a broad knowledge base about transport limitations and tailoring of electrode porosity exists, the significant influence of the electrode production process, namely speaking of the coating and drying conditions on electrode microstructure and cell performance, is often not considered. [10,[12][13][14][15] The mechanism of electrode drying according to latest knowledge is summarized in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Freeze tape casting method is also potentially useful in creating unidirectional columnar macropores in the thick cathode. 11 Groups have also focused on three-dimensional current collectors to reduce electronic travel distance. Wang et al demonstrated that ultrathick electrodes (1.2 mm thick) could be cycled more than 20 times using aluminum and copper three-dimensional foam current collectors for a LiNi 1/3 Co 1/3 Mn 1/3 O 2 cathode and graphite anode, 12 respectively.…”
mentioning
confidence: 99%
“…Freeze casting is a relatively simple alternative that overcomes many of these limitations for fabricating porous anisotropic ceramics [28][29][30], polymers [31,32], metals [33,34] or composites [35,36], often exhibiting high compressive properties [37]. This method has potential applications in cryobiology [38], remediation of contaminated media [39,40], chemical analyses [41], liquid chromatography [42], energy storage [43,44], photocatalysis [45,46], sensors [47,48], pharmaceuticals [49] and the food industry [50,51]. In this review, we highlight important aspects of external field assisted freeze casting, focusing on the theory and experimental results.…”
Section: Introductionmentioning
confidence: 99%